(untitled) - William L. Megginson; William L. Megginson (New York, 2005)
The focus of this book lies on where privatization stands today and what are the next frontiers, the why and how behind countries who privatize certain industries, whether privatization works as an economic tool and important insights relevant to financial institutions such as how to value privatized industries, how share offerings differ from private offerings, and how countries go about harnessing private capital. The book will also represent a key and unique source for information related to the details of asset sales privatization, a summary of statistics of privatized companies from 54 international stock exchanges, regulatory changes and sources for privatization information for investors, government officials, bankers and financial specialists. The volume will serve as an invaluable reference for professionals and as a core or supplementary text in privatization courses
Keywords: Privatization; Government business enterprises; Finance; Public